Pengaruh Indeks Pembangunan Manusia (IPM) dan Pertumbuhan Ekonomi terhadap Tingkat Kemiskinan di Provinsi Sumatera Barat periode tahun 2013-2018 - Radiatul Fadila; Marwan Marwan (Universitas Negeri Padang, 2020)
The purpose of this study was to determine the effect of HDI on poverty levels in Wast Sumatra, the efect of economic growth on poverty levels in West Sumatra, the effect of HDI ang economic growth on poverty levels in West Sumatra. This type of research is descriptive and associative, the data used is panel data where the research was conducted in West Sumatra in 2013-2018. This study uses the Eviews 10 Application, the model chosen is Random Effect. In the HDI variable obtained t value ≥ t-table value, meaning that there is a significant influence between HDI and poverty level. While the economic growth variable is obtained by t-count≤-t-table, meaning that there is no significant effect between economic growth on poverty levels. In addition, the F-calculated value of 40,48524 with a probability value of 0,000000≤0,05 means that there is a significant influence between the dependent variable on the independent variable. From this research, it is expected that government will further improve and equalize the quality of human resources in West Sumatra as well as a balance between capital-intensive and labor-intensive industries, so that economic growth can provide direct benefits for the people in West Sumatra.Keywords: kemiskinan, indeks pembangunan manusia, pertumbuhan ekonomi.